2016
DOI: 10.1074/jbc.m116.751271
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel d-Glycero-d-talo-oct-2-ulosonic acid-substituted Lipid A Moiety in the Lipopolysaccharide Produced by the Acetic Acid Bacterium Acetobacter pasteurianus NBRC 3283

Abstract: Acetobacter pasteurianus is an aerobic Gram-negative rod that is used in the fermentation process used to produce the traditional Japanese black rice vinegar kurozu. Previously, we found that a hydrophobic fraction derived from kurozu stimulates Toll-like receptors to produce cytokines. LPSs, particularly LPS from A. pasteurianus, are strong candidates for the immunostimulatory component of kurozu. The LPS of A. pasteurianus remains stable in acidic conditions during the 2 years of the abovementioned fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…G. bethesdensis belongs to Acetobacteraceae , the microbial family including bacteria that produce acetic acid from ethanol. Some members of this family, such as Acetobacter , have been shown to synthesize d - glycero - d - talo -oct-2-ulosonic acid (Ko) instead of 3-deoxy- d - manno -oct-2-ulosonic acid (Kdo)—a common core region constituent directly attaching to lipid A in the LPS of many Gram-negative bacteria [ 18 ]. Acid resistance of Ko has been well documented [ 22 , 23 ], and therefore, lipid A release was attempted under more acidic conditions, in the presence of 0.1 M HCl at 100–102 °C for 4.5 h. Although this harsher hydrolysis condition resulted in partial chemical degradation of the polysaccharide portion of the LPS, it substantially increased the yield of lipid A without changing its major matrix assisted laser desorption/ionization- time of flight mass spectrometry (MALDI-TOF MS) signals from those observed after mild 1% HOAc hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G. bethesdensis belongs to Acetobacteraceae , the microbial family including bacteria that produce acetic acid from ethanol. Some members of this family, such as Acetobacter , have been shown to synthesize d - glycero - d - talo -oct-2-ulosonic acid (Ko) instead of 3-deoxy- d - manno -oct-2-ulosonic acid (Kdo)—a common core region constituent directly attaching to lipid A in the LPS of many Gram-negative bacteria [ 18 ]. Acid resistance of Ko has been well documented [ 22 , 23 ], and therefore, lipid A release was attempted under more acidic conditions, in the presence of 0.1 M HCl at 100–102 °C for 4.5 h. Although this harsher hydrolysis condition resulted in partial chemical degradation of the polysaccharide portion of the LPS, it substantially increased the yield of lipid A without changing its major matrix assisted laser desorption/ionization- time of flight mass spectrometry (MALDI-TOF MS) signals from those observed after mild 1% HOAc hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Acetobacter xylinum , a cellulose-producing bacterium, possesses an LPS containing Kdo but was not analyzed immunologically [ 17 ]. Recently, in two independent studies, it was shown that Acetobacter pasteurianus NBRC3283 and A. pasteurianus CIP103108 produce a hexa-acylated lipid A with a Ko (D-gylcero-D-talo-oct-2-ulosonic acid) substitution [ 18 , 19 ]. To better understand how G. bethesdensis avoids activation of immune cells and is resistant to certain antimicrobial peptides, we purified and characterized the structure and bioactivity of the lipid A from this organism.…”
Section: Introductionmentioning
confidence: 99%
“…Acetobacter species, acetate-forming bacteria that are popular in the food industry, belong to α-Proteobacteria as well. The lipid A of A. pasteurianus was recently investigated, and some features common with those of Rhizobium and Bradyrhizobium species were elucidated ( Figure 6 ) [ 48 , 49 ]. This lipid A lacks phosphate, and the backbone is substituted by glucuronic acid and mannose at the 1 and 4′ positions, respectively.…”
Section: Diversity Of Lipid a Structure In Various Taxonomic Groupmentioning
confidence: 99%
“…This lipid A lacks phosphate, and the backbone is substituted by glucuronic acid and mannose at the 1 and 4′ positions, respectively. The backbone contains GlcN3N as a distal sugar, which was also found in Bradyrhizobium lipid A. Interestingly, the lipid A of A. pasteurianus links to the core oligosaccharide through D- glycero -D- talo -octulosonic acid (Ko) [ 48 ], which was first found in Acinetobacter LPS [ 50 ], and then in other species [ 51 , 52 , 53 ]. This sugar is deduced to stabilize the acid–labile linkage between lipid A and the core to adjust to acidic growth conditions.…”
Section: Diversity Of Lipid a Structure In Various Taxonomic Groupmentioning
confidence: 99%
“…However, the sugar moieties of the lipid A-inner core region were absent in the NMR spectra, likely due to their low flexibility, and impaired the NMR analysis. Nevertheless, the occurrence of a d-glycero-d-talo-oct-2-ulosonic acid (Ko), in place of Kdo, as the first sugar of the core OS directly linked to A. pasteurianus lipid A, [6,7] and the compositional analysis ( Figure S2), showing the presence of a 8-substituted-Kop, suggested the linkage of Kdop (K) to O8 of Ko residue, at its turn connected to the lipid A. Thus, in accordance with compositional analysis, NMR and MS data, the core region from A. pasteurianus CIP103108 ( Figure 5 and S3) possessed the following structure:…”
mentioning
confidence: 99%